No life without family: Film representations of involuntary childlessness, silence and exclusion. (1st June 2019) - Archetti, Cristina
Forming a family and having children constitutes an adulthood rite of passage, one of the tacitly assumed requirements of a fulfilled life. What happens, then, when the 'family dream' does not materialize? This article addresses the dark sides of the 'family imperative' by focusing on representations of involuntary childlessness (i.e. childlessness not by choice) in film. It advances the argument that popular culture, far from being 'mere entertainment', plays an important role in wider processes of stigmatization, silencing and, as a result, exclusion of those who do not have a family. The analysis, which is informed by a broader study into the structure of silence surrounding childlessness, presents the findings of a comparative qualitative content analysis that examined the (troubling) representations of involuntary childless individuals in 50 films from Italy, Norway and the United States. It discusses their far-reaching cultural and political implications, making practical suggestions to counter their stigmatizing effects.